Perubahan Editing dalam Microsoft Excel - Citra N. Suntik; Michella A. Lapadu; Dewi Niari; Vibriyanti K. Manembu; Ivonne M. Bonggalola; Julia T. Tondok; Selvina Rabinto; Desfika K.N. Rabinto; Rafael D. Tampi; M. Rizal Lababa (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This journal discusses the changes in editing in Microsoft Excel, the software that exists in the world. Since the launch of the ribbon interface in Excel 2007, access to editing tools has become more intuitive. The real-time collaboration feature introduced in Excel Online and Excel 2016 allows users to edit documents simultaneously, increasing work efficiency. The integration of AI technology, such as the "Ideas" feature, helps data analysis with automatic suggestions. The addition of new functions and more flexible formatting options strengthens data analysis capabilities. These changes demonstrate Microsoft's commitment to improving the user experience and relevance of Excel in modern business.